ABOUT MAKING MUSIC AND WEBSITE DESIGN, FILM, AND NOVEL LATEST USINGMACROMEDIA DREAMWEAVER MX 2004 AND PHP - Tamara Prastya Bakti (Jurnal Sistem Informasi, 2006)
Website is one of the means to deliver a new information at this time. To create a website required a variety of means of support, one that is software. Macromedia Dreamweaver MX 2004 is one of the software to design or build a website. By using Macromedia Dreamweaver MX 2004, we can create websites that look interesting that in accordance with the wishes. In addition, we can insert media from several other Macromedia. Scientific writing contains about creating and designing websites about movies, music, and latest novel featuring an interesting website, it is expected to manufacture and design of this website authors can help users of internet service to get information about movies, music, and the latest novels.